Design and experimental study of a field-reversed configuration plasma thruster prototype - HUANG, Yuxuan; ZHANG, Ming; YANG, Yong; LYU, Fangwei; YI, Xiaopeng; LYU, Chaofan; ZHANG, Yisong; RAO, Bo (Plasma science & technology, 2025)
The field-reversed configuration (FRC) plasma thruster driven by rotating magnetic field (RMF), abbreviated as the RMF-FRC thruster, is a new type of electric propulsion technology that is expected to accelerate the deep space exploration. An experimental prototype, including diagnostic devices, was designed and constructed based on the principles of the RMF-FRC thruster, with an RMF frequency of 210 kHz and a maximum peak current of 2 kA. Under the rated operating conditions, the initial plasma density was measured to be 5 × 10 17 m −3 , and increased to 2.2 × 10 19 m −3 after the action of RMF. The coupling efficiency of RMF was about 53%, and the plasma current reached 1.9 kA. The axial magnetic field changed in reverse by 155 Gauss, successfully reversing the bias magnetic field of 60 Gauss, which verifies the formation of FRC plasma. After optimization research, it was found that when the bias magnetic field is 100 Gauss, the axial magnetic field reverse variation caused by FRC is the highest at 164 Gauss. The experimental results are discussed and strategies are proposed to improve the performance of the prototype.